A theoretical model for the effective thermal conductivity of graphene coated metal foams. (October 2019) - Chan, K.C.; Tso, C.Y.; Hussain, A.; Chao, Christopher Y.H.
Highlights: A theoretical model for predicting the effective thermal conductivity was derived. The model is for graphene coated metal foam saturated with a filling medium. The derived theoretical model will be helpful in designing passive TMS. By coating with graphene, the thermal conductivity can be increased by 4.4 times. Abstract: Thermal management systems (TMS) are an integral part of electronic devices and ongoing developments using porous structures as TMS have revolutionized this field. Porous composites are extensively used for thermal management due to their light weight and high permeability. To maximize the advantages of porous structures, effective thermal conductivity calculations are critical in designing suitable TMS. Recently, we have developed a graphene coated nickel foam – paraffin composite exhibiting an improvement in thermal conductivity that is 23 times greater than pure paraffin. Current theoretical models, however, cannot predict the thermal conductivity of metal foam with the additional thermally conductive coating layer. Herein we report a theoretical model to determine the effective thermal conductivity of graphene coated metal foam saturated with a filling medium. The model is based on the 2D hexagonal structure of graphene coated metal foams. Samples with various combinations of graphene coated metal foams (nickel and copper foams with different porosities) and filling mediums (paraffin waxes and air) were prepared to validate the model. It is found that the effective thermal conductivities calculated by the model are in good agreement with the experimental results, in which the maximum deviation is less than 2%. The derived theoretical model will be helpful in designing passive TMS using porous structure (graphene coated metal foams) for heat dissipation. Parametric analysis on skeleton and graphene area ratios was also conducted. From the analysis, the node of the metal foam should be minimized. By coating the metal foam with graphene, the thermal conductivity can be increased by 4.4 times from 3.69 W/mK to 19.85 W/mK. This shows that the thin graphene coating is very effective in improving the performance of the graphene coated metal foam saturated with filler for thermal management applications.